2020
DOI: 10.5194/isprs-archives-xliv-m-1-2020-1133-2020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Characterisation of Adobe Blocks in Jojutla De Juárez, México. Seismic Vulnerability and Loss of the Earthen Architecture After the 2017 Puebla Earthquake

Abstract: Abstract. The 2017 Puebla Earthquake on 19 September struck a big part of central Mexico causing the loss of historic buildings in several states, being the state of Morelos one of the most damaged in the whole country. Jojutla de Juarez was the most affected locality of Morelos presenting important structural damages or total collapse in the built heritage, being the traditional earthen buildings, made of adobe bricks, the most vulnerable buildings to seismic efforts. Some of the causes which contributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The dwellings were fairly modified over the last decades, integrating new interior spaces with modern industrial materials and facilities, but the implementation was commonly suboptimal. The repercussions of these constructive changes were also treated in a previous research from the authors, focusing on the physical damages observed in the buildings after the earthquake [50]. The adobe buildings of Jojutla presented changes in the morphology, original uses, and architectural plans, the addition of new floor levels and construction materials, lack of maintenance, and abandonment.…”
Section: Case Study: Jojutla and The Destruction Of Its Earthen Archi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The dwellings were fairly modified over the last decades, integrating new interior spaces with modern industrial materials and facilities, but the implementation was commonly suboptimal. The repercussions of these constructive changes were also treated in a previous research from the authors, focusing on the physical damages observed in the buildings after the earthquake [50]. The adobe buildings of Jojutla presented changes in the morphology, original uses, and architectural plans, the addition of new floor levels and construction materials, lack of maintenance, and abandonment.…”
Section: Case Study: Jojutla and The Destruction Of Its Earthen Archi...mentioning
confidence: 99%
“…The estimation of the compressive strength 𝜎 or UCS (Uniaxial Compressive Strength) is obtained with the following equation: 𝜎 = (𝐶) 𝐼 𝑠(50) = 24 𝐼 𝑠 (50) (5)…”
Section: Point Load Testmentioning
confidence: 99%
“…These circumstances, in combination with catastrophic events such as the 2017 earthquakes, which caused major levels of destruction in many regions of the country, have resulted in a great loss of vernacular heritage. For instance, the adobe buildings were perceived as unsafe structures by the population [44], and the institutions and companies encouraged the users to replace their dwellings with cement blocks and modern materials.…”
Section: The Situation Of the Vernacular Architecture Of Michoacanmentioning
confidence: 99%